Anticholinergic burden in older women: not seeing the wood for the trees?. Issue 2 (2nd February 2015) - Parkinson, Lynne; Magin, Parker J; Thomson, Allison; Byles, Julie E; Caughey, Gillian E; Etherton‐Beer, Christopher; Gnjidic, Danijela; Hilmer, Sarah N; Lo, Thomas King Tong; McCowan, Colin; Moorin, Rachael; Pond, C Dimity
Abstract: Objectives: To identify medicines contributing to and describe predictors of anticholinergic burden among community‐dwelling older Australian women. Design, setting and participants: Retrospective longitudinal analysis of data from the Australian Longitudinal Study on Women's Health linked to Pharmaceutical Benefits Scheme medicines data from 1 January 2008 to 30 December 2010; for 3694 women born in 1921–1926. Main outcome measures: Anticholinergic burden calculated from Anticholinergic Drug Scale (ADS) scores derived from ADS levels (0 to 3) for all medicines used by each woman, summed over each 6‐month period (semester), medicines commonly used by women with high semester ADS scores (defined as 75th percentile of scores). Results: 1126 women (59.9%) used at least one medicine with anticholinergic properties. The median ADS score was 4 or 5 across all semesters. Most anticholinergic medicines used by women who had a high anticholinergic burden (ADS score, ≥ 9) had a low anticholinergic potency (ADS level 1). Increasing age, cardiovascular disease, and number of other medicines used were predictive of a higher anticholinergic burden. Conclusions: A high anticholinergic medicines burden in this group was driven by the use of multiple medicines with lower anticholinergic potency rather than the use of medicines with higher potency. This is a novel and important finding for clinical practice as doctors would readily identify the risk of a high anticholinergic burden for patients using high potency medicines, but may be less likely to identify this risk for users of multiple medicines with low anticholinergic potency.